Revitalizing child health: lessons from the past - Strong, KL; Requejo, J; Agweyu, A; Billah, SM; Boschi-Pinto, C; Horiuchi, S; Jamaluddine, Z; Lazzerini, M; Maiga, A; McKerrow, N; Munos, M; Schellenberg, J; et al. (Taylor and Francis, 2021)
Essential health, education and other service disruptions arising from the COVID-19 pandemic risk reversing some of the hard-won gains in improving child survival over the past 40 years. Although children have milder symptoms of COVID-19 disease than adults, pandemic control measures in many countries have disrupted health, education and other services for children, often leaving them without access to birth and postnatal care, vaccinations and early childhood preventive and treatment services. These disruptions mean that the SARS-CoV-2 virus, along with climate change and shifting epidemiological and demographic patterns, are challenging the survival gains that we have seen over the past 40 years. We revisit the initiatives and actions of the past that catalyzed survival improvements in an effort to learn how to maintain these gains even in the face of today's global challenges.